Assessing Land Use and Cover Changes arising from the 2022 water crisis in Southeast China: A comparative analysis of Remote Sensing Imagery classifications and Machine Learning algorithms - Nascimento, Eduardo Soares [UNESP]; Watanabe, Fernanda Sayuri Yoshino [UNESP]; de Lourdes Bueno Trindade Galo, Maria [UNESP]; da Silva, Erivaldo Antonio [UNESP] (Copernicus Publications, 2024)
The water crisis in the southeast region of China in 2022, caused by one of the worst heatwaves on record, was characterized by severe shortages of water resources, leading to challenges for local communities, agriculture, and industry. To analyze changes in land use and land cover (LULC) in the Jialing River region, Chongqing, China, we compared Remote Sensing (RS) imagery classifications before and after the intense heat waves of 2022. We evaluated the performance of two machine learning algorithms, KDTree KNN and Random Forest (RF), in LULC classifications. The classifications were carried out based on the RS images from the OLI/Landsat 8 system, NDWI index, and SRTM data. The model performances were similar, the classification accuracy showed that the RF algorithm was superior to KDTree KNN. The RF LULC classification and area calculation corroborate with the visual analysis, reaffirming the superiority of RF, which shows a decrease in water surface area, unlike DKTree KNN.
Keywords: and K-Nearest Neighbors Classifier; Land Use and Land Cover; machine learning; OLI/Landsat 8; random forest; remote sensing imagery